2020
DOI: 10.1136/bmjhci-2020-100133
|View full text |Cite
|
Sign up to set email alerts
|

What people share about the COVID-19 outbreak on Twitter? An exploratory analysis

Abstract: BackgroundThe recent outbreak of respiratory illness caused by COVID-19 in Wuhan, China, has received global attention as it has infected thousands of individuals there, and later it has also been reported from other countries internationally. This study aims at performing an exploratory study on Twitter to understand the information shared among the community regarding the COVID-19 outbreak.MethodsCOVID-19 related tweets were collected from Twitter using keywords from 18 January to 25 January 2020. Top-rankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
2
14
0
3
Order By: Relevance
“…In the aftermath of the Japan earthquake in 2011, the crisis communication and leadership of the government were neither clear nor apparent on Twitter [ 34 ]. Thus, crisis communication by authorities is seen as fundamental during COVID-19 [ 35 ] and authorities publish a disproportionally large number of scientifically correct tweets [ 36 ]. Previous studies have also shown that during COVID-19, tweets published by authorities are rarely among the most successful tweets [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the aftermath of the Japan earthquake in 2011, the crisis communication and leadership of the government were neither clear nor apparent on Twitter [ 34 ]. Thus, crisis communication by authorities is seen as fundamental during COVID-19 [ 35 ] and authorities publish a disproportionally large number of scientifically correct tweets [ 36 ]. Previous studies have also shown that during COVID-19, tweets published by authorities are rarely among the most successful tweets [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was some sarcasm in the negative attitudes (n=34, 3.3%) but no dark humor or personal attacks, which has been found in some other Twitter studies. This shows that the debate was generally conducted in a professional fashion, contrary to many politicized social media discussions [ 28 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 96%
“…Essas transformações consideram a explosão de tecnologias de informação em um cenário em que desponta a saúde digital, que fortalece a participação do indivíduo na construção do cuidado em saúde através da internet, sendo as redes sociais um potente espaço de empoderamento. Além da sua potencialidade, destaca-se a possibilidade do acesso às informações, sendo campo de interesse dos sistemas de saúde, tendo feito parte da estratégia de apoio dos vários países com maior controle do COVID-19, inclusive no levantamento de dados epidemiológicos e no monitoramento de casos da doença 17 . Visão esta corroborada por outros autores, como Lima 18 e Cancela 19 , que reforçam não somente o potencial das tecnologias de informação e comunicação diante da sua capacidade de alcance e celeridade na transmissão de informações, o que fez com que elas despontassem como uma das mais utilizadas atualmente, mas também como alvo das principais adaptações e inovações nos meios de comunicação e educação.…”
Section: A Potencialidade Na Divulgação E Acesso à Informaçãounclassified
“…Esses comportamentos foram influenciados pela gama de informações compartilhadas de pessoas doentes, insuficiência dos serviços de saúde, número de infectados e mortalidade, que geram ansiedade, pânico e inquietação nos indivíduos. Além disso, destacou-se que o formato das publicações também interfere no alcance e velocidade da propagação da informação, sugerindo-se a criação de conteúdos práticos e com mensagens curtas e diretas, aproveitando-se de ilustrações 17 .…”
Section: As Plataformas Digitais E Suas Dimensõesunclassified
See 1 more Smart Citation